Effects of Dark Septate Endophytes on the Performance of Hedysarum scoparium Under Water Deficit Stress - Li, Xia; He, Xue-Li; Zhou, Yong; Hou, Yi-Ting; Zuo, Yi-Ling (Frontiers in Plant Science, 2019)
Hedysarum scoparium, a species characterized by rapid growth and high drought resistance, has been used widely for vegetative restoration of arid regions in Northwest China that are prone to desertification. Desert soil is typically deficient in available water and the alleviation of drought stress to host plants by endophytes could be an efficient strategy to increase the success of desert restoration. With the objective to seek more beneficial symbionts that can be used in the revegetation strategies, we addressed the question whether H. scoparium can benefit from inoculation by dark septate endophytes (DSE) isolated from other desert plants. We investigated the influences of four non-host DSE strains (Phialophora sp., Knufia sp., Leptosphaeria sp., and Embellisia chlamydospora) isolated from other desert plants on the performance of H. scoparium under different soil water conditions. Differences in plant performance, such as plant growth, antioxidant enzyme activities, carbon, nitrogen, and phosphorous concentration under all the treatments, were examined. Four DSE strains could colonize the roots of H. scoparium successfully, and they established a positive symbiosis with the host plants depending on DSE species and water availability. The greatest benefits of DSE inoculation occurred in water stress treatment. Specifically, Phialophora sp. and Leptosphaeria sp. improved the root biomass, total biomass, nutrient concentration, and antioxidant enzyme activities of host plants under water deficit conditions. These data contribute to the understanding of the ecological function of DSE fungi in drylands.